Optimal Duration of Oral Sildenafil for Perioperative Management of Severe Pulmonary Hypertension in Mitral Valve Replacement - CHEEMA, SALIK AHMED CHEEMA; MIKRANI, BENAZEER; JUMADIN, ANEELA JUMADIN; MAHMOOD, MUHAMMAD MOHSIN; YASIR, MUHAMMAD YASIR; NIAZI, ATTAULLAH KHAN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Rheumatic heart disease (RHD) involves the mitral valve in 50–60% of cases. Long-term mitral valve pathologies cause multiple sequelae in the form of atrial fibrillation, pulmonary hypertension, and heart failure. Sildenafil has been used as a therapy for the control of pulmonary hypertension, with emphasis on the perioperative period. Aim: To investigate the influence of oral administration of sildenafil at different durations on intraoperative and postoperative pulmonary hypertension and to compare these effects with preoperative pulmonary pressures. Methods: This comparative cross-sectional study was conducted at Department of Cardiac Surgery, King Edward Medical University/ Mayo Hospital Lahore between July 2024 and January 2025. Patients were divided into 2 groups. Patients enrolled in the short course of sildenafil were administered oral Sildenafil 50mg/5ml, 3 times a day for 2 days before surgery. And in the long course, the same regimen was given for 7 days. Results: A Mann-Whitney U test showed that there was no significant difference in the preoperative mean pulmonary artery pressures between the groups receiving the short and long course of oral sildenafil (p-value 0.890). The reduction in mean pulmonary artery pressures from preoperative to postoperative was analyzed to be 16.46 ± 4.13 for the short course whereas it was 24.83 ± 5.04 for the long course and the difference between these two results was found to be statistically significant (p< 0.05, p< 0.001). Conclusion: Sildenafil has been shown to be effective in the perioperative management of pulmonary hypertension in mitral valve surgery with longer duration of sildenafil administration leading to greater reduction in pressures.